Diabetic Nephropathy: Pathogenesis, Mechanisms, and Therapeutic Strategies - Dwivedi, Shivangi; Sikarwar, Mukesh Singh (Hormone and Metabolic Research, 2024)
Diabetic nephropathy represents a predominant etiology of end-stage renal disease (ESRD) on a global scale, significantly impacting the morbidity and mortality rates of individuals with diabetes. The primary objective of this analysis is to furnish a comprehensive examination of the etiology, fundamental mechanisms, and treatment modalities for DN. The development of DN stems from a multitude of factors, encompassing a intricate interplay involving metabolic irregularities induced by hyperglycemia, alterations in hemodynamics, inflammatory responses, oxidative stress, and genetic susceptibility. Principal mechanisms encompass the generation of advanced glycation end products (AGEs), activation of protein kinase C (PKC), and overexpression of the renin-angiotensin-aldosterone system (RAAS). These processes precipitate glomerular hyperfiltration, hypertrophy, and eventually, fibrosis and scarring of the renal parenchyma. Initially, hyperglycemia triggers mesangial proliferation and thickening of the glomerular basement membrane in the incipient stages of DN, subsequently leading to progressive glomerular sclerosis and tubulointerstitial fibrosis. Inflammatory cascades, notably involving cytokines like TGF-β and NF-κB, play pivotal roles in the advancement of DN by fostering the accumulation of extracellular matrix and renal fibrosis. Inflammation pathways, particularly those involving cytokines like TGF-β and NF-κB, play essential roles in diabetic nephropathy progression by stimulating extracellular matrix accumulation and renal fibrosis. The presence of oxidative stress, worsened by dysfunctional mitochondria, contributes further to renal injury via lipid peroxidation and DNA damage. Current therapeutic approaches for diabetic nephropathy concentrate on optimizing glycemic control, controlling hypertension, and suppressing the renin-angiotensin-aldosterone system. Among antihypertensive medications, ACE inhibitors and angiotensin II receptor blockers are crucial for decelerating disease advancement.
Keywords: diabetic nephropathy; antihypertensive agents; ACE inhibitors and angiotensin II receptor; oxidative stress; advanced glycation end products